SAT0670 Dynamic thiol/disulfide homeostasis as a novel oxidative marker in behÇet's disease. (12th June 2018) - Can Sandikci, S.; Colak, S.; Omma, A.; Enecik, M.E.; Ozbalkan, Z.; Neselioglu, S.; Erel, O.
Abstract : Background: Behçet's disease (BD) is a relapsing systemic inflammatory disorder of unknown etiology. 1 Objectives: In this study, we aimed to evaluate the relationship between the thiol-disulfide balance and disease activity and organ involvement in BD. Methods: One hundred fifty (150) patients with BD and 100 age-gender matched healty controls were included in the study. Disease activity was assessed with the BD Current Activity Form (BDCAF) score. Serum levels of native thiol (NT), total thiol (TT), and disulfide were measured and the disulfide/native thiol, disulfide/total thiol and native thiol/total thiol levels were calculated for the patient and control groups. Results: NT, TT, NT/TT values of the BD patients were significantly lower than those of the control group. The disulfide/NT, disulfide/TT values of BD patients were higher compared to the control group and the disulfide value of the BD group was slightly higher compared to the control group (table 1). No correlation was determined between thiol levels and disease activity and organ involvement in BD. Conclusions: In patients with Behcet's disease, the dynamic thiol-disulfide homeostasis balance shifted towards disulfide formation due to thiol oxidation. It may be used as a novel marker in BD because it is easy, practical, fully automated and relatively inexpensive. Acknowledgements: The authors thank staff of Ankara Numune Training and Research Hospital, Department of Rheumatology for their generous friendly assistance in every step of this study. Disclosure of Interest: None declared